Pengaruh Metode Pembelejaran Diskusi Buzzgroup terhadap Keaktifan dan Prestasi Belajar Siswa - Apriyanti, Nurvilia; Herayanti, Lovy; Habibi, Habibi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This study was conducted to determine the effect of buzz group discussion learning methods on the activeness and learning achievement of physics in class VIII of SMPN 4 Praya Barat Daya 2015/2016 Academic Year. The type of research used in this study is a kind of quasi-experimental research. The population in this study were all eighth-grade students totaling 38 people consisting of class VIII A totaling 20 people as the experimental class and class VIII B totaling 18 people as the control class with the sampling technique used was a saturated sampling technique. The instruments used are valid observation and test sheets both in content, construct, and empirical with a value of 3.34; 3.40; and 3.23, and reliable with the value of Î±Cronbach = 0.608. The results of this study were also able to influence the achievement of learning physics. Based on statistical calculations using the ttest test, the value of tcount = 23.00 is greater than t table = 2.02 (t count = 23.00> t table = 2.02). Thus, it can be concluded that there is the influence of buzz group discussion learning methods on the activeness and learning achievement of physics in class VIII Praya Barat Daya SMP 4 2015/2016 Academic Year.